Novel rotating cone viscous micro pump. (1st January 2013) - Bataineh, Khaled M.; Taamneh, Yazan
This paper presents numerical solution for Navier-Stokes equations coupled with energy equation for gaseous slip flow between two concentric micro rotating cone pump. The inner cone is rotating while the outer is held stationary. A first-order slip boundary condition is applied. The effect of Kn, rotational speed and cone angle on pressure rise, flow rate, coefficient of moments and pump efficiency are studied. Slip values are found to be major parameters that affect the performance of pump. Four values of Kn are studied; Kn = 0, 0.001, 0.01 and 0.1. Optimal pump performance corresponds to Kn = 0.01. For all values of Kn, pressure rise is inversely proportional to flow rate. Increasing Kn reduces the slope of Δ P – Q curves. Both maximum flow rate and maximum pressure rise increase with rotational speed. Three values of cone angle b were studied, namely, 9°, 14° and 18°. Optimal performance is obtained for b = 14°.